2020
DOI: 10.1111/dar.13027
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of purchasing and payment mechanisms in alcohol and other drug treatment services in Australia: A qualitative study involving alcohol and other drug service providers and purchasers of treatment

Abstract: Introduction and Aims. Governments across the globe invest considerable amounts in funding alcohol and other drug (AOD) treatment. Little attention however has been paid to the ways AOD service providers are chosen and how they are paid. This study sought to examine the perceptions of Australian AOD treatment purchasers and providers regarding different purchasing and payment mechanisms. Design and Methods. Qualitative interviews with AOD treatment providers and purchasers (N = 197) were undertaken across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Service providers recognised sustained engagement is needed to build relationships and facilitate conversations about AOD use with young people and their broader communities. A previous program that targeted young men from African backgrounds who were disengaged from education and employment identified that short-term programmes do not enable adequate time for building relationships and addressing complex challenges (Turnbull & Stokes, 2011) These constraints reflect challenges in the broader AOD sector with short-term and irregular funding recognised as barriers to service delivery (van de Ven et al, 2020). Additionally, demonstrating progress towards outcomes can be challenging when greater value is placed on abstinence or reduced consumption as opposed to improvements in health and quality of life (Savic & Fomiatti, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Service providers recognised sustained engagement is needed to build relationships and facilitate conversations about AOD use with young people and their broader communities. A previous program that targeted young men from African backgrounds who were disengaged from education and employment identified that short-term programmes do not enable adequate time for building relationships and addressing complex challenges (Turnbull & Stokes, 2011) These constraints reflect challenges in the broader AOD sector with short-term and irregular funding recognised as barriers to service delivery (van de Ven et al, 2020). Additionally, demonstrating progress towards outcomes can be challenging when greater value is placed on abstinence or reduced consumption as opposed to improvements in health and quality of life (Savic & Fomiatti, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One consequence of competitive tendering is service providers having multiple funders. Views of Australian treatment providers were mixed regarding having multiple funders—on one hand, having multiple funders was seen to protect agencies from ‘political whim’ ([9], p. 194); on the other hand, it was regarded as a ‘drain on organizational resources’ ([9], p. 194). Multiple contracts for a single provider are also seen in the Nordic countries.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, both service providers and treatment purchasers have expressed similar concerns about the ubiquity of competitive tendering as a selection process for service providers [9]. One consequence of competitive tendering is service providers having multiple funders.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on market-orientation in the field of substance use have been conducted in a number of countries, primarily in Europe and Australia. These studies tend to direct their principal focus at organisational policies linked to payment or reimbursement systems (Jones et al, 2018;Nesvaag & Lie, 2010;Roman et al, 2006;Shepherd et al, 2014;van de Ven et al, 2020), although some studies have focused on the effect of NPM on staff working in substance use treatment (Lewiskin, 2018). Few studies have focused on examining different forms of substance use care delivery from a staff or patient perspective however (van de Ven et al, 2020).…”
Section: Market Orientation and Patient Choice In Substance Use Treatmentmentioning
confidence: 99%
“…These studies tend to direct their principal focus at organisational policies linked to payment or reimbursement systems (Jones et al, 2018;Nesvaag & Lie, 2010;Roman et al, 2006;Shepherd et al, 2014;van de Ven et al, 2020), although some studies have focused on the effect of NPM on staff working in substance use treatment (Lewiskin, 2018). Few studies have focused on examining different forms of substance use care delivery from a staff or patient perspective however (van de Ven et al, 2020). The delivery forms that often constitute the focus of studies in the field of marketbased service provision are results-oriented models, such as payment by results, or public procurement, i.e.…”
Section: Market Orientation and Patient Choice In Substance Use Treatmentmentioning
confidence: 99%